Spatial distribution, enzymatic activity, and insecticide resistance status of Aedes aegypti and Aedes albopictus from dengue hotspot areas in Kuala Lumpur and Selangor, Malaysia - Wan Najdah Wan Mohamad Ali,; Rohani Ahmad,; Zurainee Mohamed Nor,; Ahmad Fakhriy Hassan, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
The effectiveness of insecticide-based dengue control interventions is very much influenced by the insecticide resistance status of the mosquito at the targeted areas. This study aims to determine the insecticide resistance status and the enzymatic activity. WHO adult bioassays conducted on Ae. aegypti and Ae. albopictus from 12 dengue hotspots outbreak areas in Kuala Lumpur and Selangor towards insecticides currently and historically used for mosquito control in Malaysia which include two pyrethroids, one organoclorine, one organophosphate and one carbamate. Biochemical enzyme assays were conducted and the activity of enzymes αEsterase, MFO, GST and AChE were examined. Kruskal-Wallis H, Mann-Whitney U and ANOVA test were used to determine the significant difference of the mortality between insecticides and localities, the enzymes activity between the field and the lab strains, and the enzymes activity within all field strains. Ae. aegypti from all sites have developed resistance towards all tested insecticides based on WHO adult bioassays; permethrin, DDT, malathion and propoxur. The result of biochemical enzyme assays demonstrated that the activity of enzymes was altered. α-esterase and MFO were altered in both species from all areas. GST was altered in both species as well except in Ae. albopictus from sites Bandar Rinching and Taman Gombak Setia. AChE was found significantly demoted in Ae. aegypti from Sri Nilam Shah Alam and Ae. albopictus from Flat Sri Labuan Cheras only. The resistance detected might be the result of activity by either single or several enzymes combined. The development of resistance is mainly via metabolic mechanism.